ANALISIS PEMBIAYAAN MURABAHAH PADA KOPERASI JASA BERKAH BERSAMA SYARIAH KOTA BENGKULU - Mukadar, Amir; Dharma Setiawan; Nazar; Muhammad Said Romadhon (Universitas Muhammadiyah Bengkulu, 2023)
Cooperative is an institution in the form of economic organization owned and operated by its members. The main goal of cooperatives is to improve the welfare of members through cooperation and active participation in economic endeavors. The sharia cooperative is a form of cooperative that operates based on sharia principles. These principles cover the aspects of finance, transactions and Islamic values that are recognized globally. In implementing sharia cooperative financing, it must comply with syar'i aspects and economic aspects, which means that in every realization of financing to members of sharia cooperatives it must still be guided by Islamic law, including not containing elements of gharar, maysir, and usury and the business sector is halal, while still considering the acquisition of profits for sharia cooperatives and the members themselves. This research is a field research that uses a qualitative descriptive method. Where the data sources are primary and secondary obtained by interviews, observation and documentation. Data processing begins with correcting the data, followed by rearranging the data and analyzing existing data in order to find results as answers to the problem formulation. Based on the research results, the Bengkulu City Sharia Berkah Bersama cooperative provides murabahah contract financing to its members in accordance with the DSN-MUI Fatwa which regulates the conditions for murabahah financing, such as making a contract that is free of usury, purchasing goods on behalf of the cooperative, and conveying information regarding purchases to members.